Skreening Potensi Antibakteri pada Beberapa Spesies Rumput Laut terhadap Bakteri Patogen pada Udang Windu - Izzati, Munifatul - (Bioma : Berkala Ilmiah Biologi, 2007)
Antibacterial activity of several local seaweeds has been screened. Most of these seaweeds species showantibacterial properties against pathogenic bacteria from species of Vibrio and Pseudomonas. The activity ofseaweeds extracts were determined by type of solvent used in extraction. Respond of each pathogenic bacteria werealso different to each type of extract. Most seaweeds show stronger activity against Pseudomonas rather than Vibrio.Caulerpa and Padina were more active against Pseudomonas compared to Sargassum and Gelidium. Compared toother seaweeds, Sargassum and Gelidium were more active against Vibrio. It is predicted that Sargassum is the themost suitable to be used in polyculture with tiger shrimp (Peneaus monodon), as this is the most active against themost dangerous pathogenic bacteria, Vibrio harveyi. Beside that, the active component of Sargassum is solved inwater, therefore will be easier to diffuse into shrimp pond.